3D temperature gradient effect on a steel–concrete composite deck in a suspension bridge with field monitoring data. Issue 7 (17th April 2018) - Wang, Da; Liu, Yongming; Liu, Yang
Summary: Spatial and temporal temperature variations are critical for the accurate stress analysis of a suspension bridge with a steel–concrete composite deck system. This issue has been widely investigated in recent years in the open literature. In current codes, only the vertical temperature gradient (VTG) is considered in the thermal stress calculation. A complete 3D temperature profile has rarely been investigated. In the proposed study, the Aizhai Suspension Bridge with a steel–concrete composite deck system in China was investigated to determine the realistic 3D temperature‐gradient distributions and their effects on the structural performance using a finite element method. First, the distributions of the spatial‐temperature gradient including the VTG, the transversal temperature gradient (TTG), and the longitudinal temperature gradient (LTG) were investigated based on a structural health monitoring system. The results showed that the values of these gradients were far greater than those suggested by the Chinese code. Next, a 3D finite element model was proposed to investigate the thermal stress variation in the steel–concrete composite bridge deck system. The thermal‐induced stresses due to the VTG, TTG, and LTG were obtained using the monitored temperature data and the proposed 3D finite element model. The coupling effects of the 2D (coupling of the VTG and TTG) and 3D (coupling of the VTG, TTG, and LTG) temperature gradients were obtained and compared with those of the 1D approximation and Chinese code. Possible reasons for the 3D temperature‐gradient effect were also discussed. Following this, conclusions and recommendations for future bridge analysis and design were provided based on the proposed study.